Peroxidase Release Induced by Ozone in Sedum album Leaves: Involvement of Ca(2+) - Castillo, Federico J. (1984)
The effect of ozone was studied on the peroxidase activity from various compartments of Sedum album leaves (epidermis, intercellular fluid, residual cell material, and total cell material). The greatest increase following a 2-hour ozone exposure (0.4 microliters O(3) per liter) was observed in extracellular peroxidases. Most of the main bands of peroxidase activity separated by isoelectric focusing exhibited an increase upon exposure to ozone. Incubation experiments with isolated peeled or unpeeled leaves showed that leaves from ozone-treated plants release much more peroxidases in the medium than untreated leaves. The withdrawal of Ca(2+) ions reduced the level of extracellular peroxidase activity either in whole plants or in incubation experiments. This reduction and the activation obtained after addition of Ca(2+) resulted from a direct requirement of Ca(2+) by the enzyme and from an effect of Ca(2+) on peroxidase secretion. The ionophore A23187 promoted an increase of extracellular peroxidase activity only in untreated plants. The release of peroxidases by untreated and ozone-treated leaves is considerably lowered by metabolic inhibitors (3-(3,4-dichlorophenyl)-1,1-dimethylurea and sodium azide) and by puromycin.